Correlation of gender and age with serum adipokines level in north indian adults - Kumar, Pravesh; Srivastava, Neena; Tiwari, Sunita; Verma, Narsingh; Pandey, Shivani; Porwal, Naveen Bhartia; Kumar, Pradeep; Rahul, Dr. (Asian Journal of Medical Sciences, 2015)
Objective: There are two forms of adipose tissue, brown adipose tissue (BAT) and white adipose tissue (WAT). Distribution of adipose tissue differs in different gender and different age group. Adipose tissue expresses various secretary proteins, including leptin and adiponectin, collectively called adipokines. The purpose of this study to elucidated the correlation of serum leptin, serum adiponectin levels with age and gender in north Indian population. Materials and Methods: 100 subjects (55 male, 45 female) aged between 18?25 yrs were included in the study. Blood sample were taken after overnight fasting for biochemical assay. Serums were separated by centrifugation method. Serum leptin and serum adiponectin were analyzed by using RayBio ELISA Kit. Result: The serum leptin (pg) was significantly (p=0.001) higher among female (428.28±83.06) subjects compared with males (365.42±102.56). Similarly, serum adiponectin (pg) level was also significantly (p=0.02) higher among females (5313.15±1151.12) than males (4794.72±1078.38). The age was mildly and negatively correlated with Serum adiponectin (r= -0.317, p=0.001) and had no correlation with serum leptin levels. Conclusion: Serum adipokines levels in young north Indian adults are influenced by gender and age of subjects, suggests that female subject, relative to the males, are at increased risk for obesity-related metabolic co-morbidities. DOI: http://dx.doi.org/10.3126/ajms.v6i5.11862 Asian Journal of Medical Sciences Vol.6(5) 2015 9-11